BROWN BEAR (URSUS ARCTOS) POPULATION DENSITY IN THE EASTERN BLACK SEA MOUNTAINS IN TURKIYE - Baskaya, E.; Gundogdu, E.; Baskaya, S. (Aloki Applied Ecological Research and Forensic Inst Ltd, 2022)
Brown bear (Ursus arctos) population density has not been determined so far in the Eastern Black Sea Mountains, Tiirkiye, where the most fatal attacks are experienced in the country. Therefore, in order to determine the bear population density, studies were carried out from 2008 to 2017 in 12 sampling sites with a total area of 900 km(2). Field studies were carried out in all sampling sites, in groups of 2-4 people, generally by establishing tented camps. In addition, 5 comprehensive inventory studies were conducted with groups of 10-30 people in 3 of these sampling sites. Direct and indirect counting methods were used together in all inventories in the sampling sites. Direct counts were performed using line counting, point counting, camera traps and thermal camera Indirect counts are the recording of tracks and signs. As a result of the study, while the population density of bears in the sampling sites varied between 40-466 bears/1000 km2, the average density was determined as 194 bears/1000 km2. The population size of bears in the study area, which is approximately 28,000 km(2), was calculated as 5432 individuals, of which 3259 are adults and 2173 are cubs and yearlings.
Keywords: bear inventory; point count; camera trap; thermal camera; footprint